Comparative assessment of profilometric indicators of the lower part of the face in adult patients with congenital nonunions of the upper lip and palate before and after orthopedic treatment. - Oliinyk М. Ю.; Oliinyk Адріан Юрійович (Actual Dentistry, 2024)
Topicality. Despite the search for diverse options for medical and social care for people with congenital cleft upper lip and palate after surgical interventions in adulthood, there are still problems related to the specifics of orthopedic treatment for such patients that need to be resolved. An important criterion for evaluating the effectiveness and success of treatment of patients with congenital cleft upper lip and palate is the improvement of their quality of life in the process of complex rehabilitation. One of the possible options for improving the quality of life of such patients and their social adaptation is orthopedic rehabilitation using numerous options for orthopedic designs of dentures, which reproduce both functional and, in part, aesthetic capabilities. The aim of the study. To conduct a comparative assessment of the presence of facial profile aesthetics before and after orthopedic rehabilitation of patients with congenital cleft upper lip and palate after surgical interventions. Materials and methods. A comparative assessment of the aesthetics of the face profile before and after orthopedic rehabilitation of 37 patients aged 17 to 42 years with congenital cleft upper lip and palate (CCULP) after surgical interventions was carried out. Researched: ratio in the area of the frontal height of the face (N-Sn-Gn), nasolabial angle (C-Sn-UL), conducted lip analysis according to Ricketts, as well as the angle between the line that passed through points (N-Pog’) and Ricketts’ line (aesthetic line) and profile concavity angle (G-An Pog’) before and after orthopedic treatment as a percentage of these indexes. Conclusion. The analysis of the parameters of the profile of the lower part of the face, in particular the parameters of the lips according to Ricketts and the nasolabial angle, testify that as a result of orthopedic rehabilitation of patients with CCULP, regardless of the type of nonunion, both fixed and removable (combined) prosthetics, the profile of the lower part of the face improved significantly, which affected aesthetic parameters of the face.